1945
DOI: 10.1172/jci101611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Venesection and the Pooling of Blood in the Extremities on the Atrial Pressure and Cardiac Output in Normal Subjects With Observations on Acute Circulatory Collapse in Three Instances 1

Abstract: The mechanisms by which the body compensates for a decrease in blood volume have not been thoroughly studied in man. All physicians are aware that from 500 to 1000 ml. of blood can be removed from a person of average size without producing any symptoms, if the body is horizontal. If the blood is removed rapidly, hemodilution plays little part in the immediate adjustment. Do the arterioles constrict, maintaining the arterial pressure at a normal level at the expense of blood flow to the tissues? Is the atrial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

1946
1946
1971
1971

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(36 citation statements)
references
References 5 publications
3
31
0
1
Order By: Relevance
“…The response of cardiac output to transfusion in the control studies reported herein is in agreement with the findings of those investigators (2-4, 6, 7) who have observed that the cardiac output is neither increased consistently by large intravenous infusions, nor decreased by venesection of 300 to 900 ml or by the trapping of blood in the extremities (16). In the absence of Arfonad infusion, the large transfusion was not associated with a significant increase in central blood volume.…”
Section: Discussionsupporting
confidence: 92%
“…The response of cardiac output to transfusion in the control studies reported herein is in agreement with the findings of those investigators (2-4, 6, 7) who have observed that the cardiac output is neither increased consistently by large intravenous infusions, nor decreased by venesection of 300 to 900 ml or by the trapping of blood in the extremities (16). In the absence of Arfonad infusion, the large transfusion was not associated with a significant increase in central blood volume.…”
Section: Discussionsupporting
confidence: 92%
“…McMichael and his group (19) have promulgated the idea that within physiological limits in the compensated heart, the cardiac output changes concordantly with right auricular pressure but this concept has recently been criticized (20,21). In our experiments there was no relationship between mean right auricular pressure and stroke volume, pulmonary arterial pressure, blood pressure or work of the right heart in either the cooled or the control series.…”
Section: Right Auricular and Pulmonary Arterial Pressuresmentioning
confidence: 45%
“…(3) Comparison of the pulse and blood pressure changes found in the normal subjects during these LBNP exposures with the changes reported from bleeding studies suggests that over 10 ml per kilogram of body weight (over 760 ml) had been removed from the effective blood volume in the normal subjects. [21][22][23][24] The circulatory changes induced by LBNP in the heart failure patients seem sufficient to conclude that a significant degree of hypovolemia had been induced, but the amount of blood sequestered from the central circulation in this group cannot be estimated with accuracy for three prime reasons: (1) The amount of blood impounded in the lower body may not be equal in the two groups because of the altered vascular and extravascular compliance in patients with heart failure due to congestion and edema and altered neurohumerol activity; (2) because of the increased total blood volume usually associated with heart failure, an equal volume of sequestered blood may not represent an equivalent decrement in effective blood volume and may thus provide a lesser circulatory stress; (3) the cardiovascular system in heart failure patients may respond differently to an equivalent degree of hypovolemia because of the altered activity of the sympathetic nervous system and levels of vasoactive hormones, the administration of drugs affecting the circulation, and local-tissue metabolic changes due to inadequate perfusion.…”
Section: Methodsmentioning
confidence: 99%